USING HYPNOTEACHING TECHNIQUE TO EMPOWER STUDENTS’ COURAGE IN SPEAKING SKILL - Budi Rianto (Journal of English Education Program (JEEP), 2020)
This research discusses about using Hypnoteaching technique to empower students’ courage in speaking skill. This research gives enlightenment to help empowering students speaking skill through Hypnoteaching technique. The objective of this study was aimed to figure out how Hypnoteaching technique empower students’ courage in speaking skill, and what are the students and teacher’s perceptions towards Hypnoteaching technique. The present study used qualitative Case study design. Twenty-eight students from eleventh grade and an English teacher were participated in this study. The data were obtained through observation to observe how teacher implemented Hypnoteaching as a technique in teaching speaking, questionnaire and interview to collect data about students and teacher’s perceptions towards Hypnoteaching technique. To analyze the observation data and interview, the researcher first transcribed and then made interpretation from it. The questionnaire data was analyzed using Likert Scale measurement. The findings revealed that the teacher implement Hypnoteaching in teaching speaking, and she also uses constructivism learning model in teaching activity. In addition, Hypnoteaching technique can make them more motivated and courageous in speaking English. Based on the findings, the researcher suggested in any case of their subject, teachers should implement an effective, easy and enjoyable technique especially Hypnoteaching in their teaching activity, not only to motivate the students but also to empower their courage and knowledge particulary in speaking class.Keywords: Hypnoteaching, Technique, Speaking.